PERAN SUASANA TOKO TERHADAP PEMBELIAN IMPULSIF (STUDI PADA MATAHARI CILANDAK TOWN SQUARE) - Mamlu Atul Hasanah (2017)
mpulsive purchases is one factor, which is considered by retailer and manufacturer. The purpose of this study was to determine the role of positive emotions in mediating the store atmosphere on impulsive purchases. The population in this study is that cilandak west village community which ever do impulsive purchases in Matahari Cilandak Town Square. The size of the samples taken as many as 50 people, with a non-probability sampling method particularly purposive sampling. Data collected through questionnaires. The data analysis technique used is the method of analysis PLS (Partial Least Square). These results indicate that the store atmosphere has a positive and significant impact on impulsive purchases at 0,387. Indirect effect store atmosphere of impulsive purchases through positive emotion at 0,431. Hence indirect effect have more impact of the direct effect.